Predicting Mental Health Based on Identity, Parent-Child Relationships and Religious Attitudes of Adolescents Girls - Zamani , Sedighe; Hadian , Ali; Gorji , Yousef (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to predict mental health based on identity styles, parent-child relationships, and adolescents’ religious attitudes. Method: This study’s statistical population was 5800 adolescent girls aged 15 to 18 years who were studying in the second year of high school in the academic year of 2019 in Najafabad. Among these individuals, a sample of 361 students was selected by multi-stage random cluster sampling, according to the Morgan table. In this study, General Health Questionnaire (Goldberg and Hillier, 1972), Identity Style Inventory (Berzonsky, 1992), Child-Parent Relationship Scale (Pianta, 1994), and Religious Orientation Scale (Golriz and Baraheni, 1974) were used to collect data. Results: The results showed that the information identity style was negatively correlated with mental health, and normative and diffuse-avoidant identity styles were positively correlated with mental health. There is also a significant positive correlation between child-parent relationships and mental health. Also, there is a significant positive correlation between religious attitude and mental health. Information identity style with beta coefficient (β=0.18), normative identity style with beta coefficient (β=0.28), diffuse-avoidant identity style with beta coefficient (β=0.25), child-parent relationships with coefficient Beta (β=0.23) and religious attitude with beta coefficient (β=0.18) were able to predict mental health. Conclusion: Identity styles, child-parent relationships, and religious attitudes affect the mental health of female students. Therefore, it is recommended to improve the quality of identity styles and religious attitudes by giving parents the necessary training.